2015
DOI: 10.1016/j.resuscitation.2015.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Volume versus outcome: More emergency medical services personnel on-scene and increased survival after out-of-hospital cardiac arrest

Abstract: a b s t r a c tBackground and aim: : The large regional variation in survival after treatment of out-of-hospital cardiac arrest (OHCA) is incompletely explained. Communities respond to OHCA with differing number of emergency medical services (EMS) personnel who respond to the scene. The effect of different numbers of EMS personnel on-scene upon outcomes is unclear. We sought to evaluate the association between number of EMS personnel on-scene and survival after OHCA. Methods: We performed a retrospective revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 17 publications
0
27
2
1
Order By: Relevance
“…The number and proportion of EMTs on the scene for OHCA resuscitation has remained a modifiable factor linked to ROSC [13][14][15][16][17]. Until now, the influences of the EMT configuration on outcomes of OHCA patients remain controversial.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The number and proportion of EMTs on the scene for OHCA resuscitation has remained a modifiable factor linked to ROSC [13][14][15][16][17]. Until now, the influences of the EMT configuration on outcomes of OHCA patients remain controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, the influences of the EMT configuration on outcomes of OHCA patients remain controversial. Sam A. Warren et al and Kajino et al both indicated that the number of EMTs was associated with survival rate and even neurological outcome in patients with OHCA [13,14], whereas Hagiwara S. et al and Eschmann NM et al found opposite results [15,16]. In our cohort, the association of EMT number and patient outcomes, in terms of sustained ROSC, survival to discharge, and favorable neurologic status at discharge, were trivial after adjustment for all the independent predictors of sustained ROSC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…19 These covariates were chosen a priori based on their known associations with survival from prior studies of OHCA, biologic plausibility, and adequate ascertainment. 11, [15][16][17][18][19][20][21][22][23]…”
Section: Key Pointsmentioning
confidence: 99%